An Odyssey into the World of Enzymes - Adewale, Isaac Olusanjo (My University, 2023)
An Inaugural Lecture Delivered at Oduduwa Hall, Obafemi Awolowo University, Ile-Ife, Nigeria on Tuesday, 14th March, 2023 by Isaac Olusanjo Adewale, Professor of Biochemistry Inaugural Lecture Series 369
An Inaugural Lecture Delivered at Oduduwa Hall, Obafemi Awolowo University, Ile-Ife, Nigeria on Tuesday, 14th March, 2023 by Isaac Olusanjo Adewale, Professor of Biochemistry Inaugural Lecture Series 369